1980
DOI: 10.1095/biolreprod23.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Proteins of Epididymal Origin with Spermatozoa

Abstract: The present work was devoted to the study of certain aspects of the interaction of rat specific epididymal proteins (SEP) with spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 30 publications
5
76
0
1
Order By: Relevance
“…Rat CRISP1 (rCRISP1) is synthesized in an androgen-dependent manner by the proximal segments of the epididymis, and associates with the sperm surface during epididymal maturation (Kohane et al, 1980a;Kohane et al, 1980b). Originally localized in the dorsal region of the sperm head, rCRISP1 migrates to the equatorial segment as the acrosome reaction occurs (Rochwerger and Cuasnicu, 1992).…”
Section: Epididymal Crisp1mentioning
confidence: 99%
“…Rat CRISP1 (rCRISP1) is synthesized in an androgen-dependent manner by the proximal segments of the epididymis, and associates with the sperm surface during epididymal maturation (Kohane et al, 1980a;Kohane et al, 1980b). Originally localized in the dorsal region of the sperm head, rCRISP1 migrates to the equatorial segment as the acrosome reaction occurs (Rochwerger and Cuasnicu, 1992).…”
Section: Epididymal Crisp1mentioning
confidence: 99%
“…Previous results had indicated that about 70 % of the total protein DE associated with cauda epididymal spermatozoa was lost from the cells when these were capacitated for 4 h in utero (Kohane et al, 1980 It is accepted that the postacrosomal region of the sperm plasma membrane is a specialized structure through which fusion with the oocyte membrane is started (Bedford and Cooper, 1978 ;Salgi and Phillips, 1980). In addition, it is also well established that a considerable degree of species specificity is retained by this step of membrane fusion in many mammals (Hanada and Chang, 1972 (Tezon et al, 1982).…”
mentioning
confidence: 99%
“…Current evidence suggests that specific secretory proteins in the epididymis play an important role in the development of motility (Acott and Hoskins, 1978) and surface properties of spermatozoa during their post-testicular maturation stage (Kohane et al, 1980 ;Jones et al, 1980 b ;Voglmayr et al, 1980 ;Orgebin-Crist et al, 1981). It has been demonstrated in rats and rabbits that different proteins are synthesized and secreted in different morphological regions of the epididymis and that some of these proteins are regulated specifically by androgen (Lea et al, 1978 ;Brooks and Higgins, 1980 ;Faye et al, 1980 ;Moore, 1980 ;Jones et al, 1980Jones et al, a, 1981.…”
mentioning
confidence: 99%